PERILAKU BIROKRAT DALAM PELAYANAN PUBLIK PADA KANTOR DESA GETASREJO KECAMATAN GROBOGAN KABUPATEN GROBOGAN - Andan Jatmiko, Muhammad Sinung (JI@P, 2024)
Practices in the process of providing public services in Indonesia today are still filled with uncertainty regarding time, costs and methods of service. Costs and service times are not clear to service users. This often happens because service procedures do not regulate the obligations of service providers and also the rights of community members as service users themselves. Apart from that, we also often see and hear actions and behavior of Village Officials in providing services that are less polite, less friendly and sometimes there are also actions that are discriminatory in nature. This study used qualitative research methods. Qualitative research is research that contains descriptive research and tends to use analysis. The aim of this research is to find out how the behavior of bureaucrats in Getasrejo Village is related to the care, discipline and responsibility of bureaucrats in serving the community in Getasrejo Village, Grobogan District, Grobogan Regency. The results of this research can be concluded that the behavior of bureaucrats in Getasrejo Village still needs to be improved so that The community really gets maximum service. This can be seen from: 1) There is still a lack of concern for the community because there are still discriminatory actions and the community will have more confidence in the performance of the authorities if there is transparency and professionalism in data collection. 2) Village officials' discipline is also still lacking. because we often find ourselves arriving late to the office, leaving early and the dress code is sometimes not adhered to. 3) In terms of responsibility, there needs to be good cooperation, supervision and firm action towards officers in carrying out their duties so that social jealousy does not create